Moodle 1.9 top extensions cookbook : over 60 simple and incredibly effective recipes for harnessing the power of the best Moodle modules to create effective online learning sites /: over 60 simple and incredibly effective recipes for harnessing the power of the best Moodle modules to create effective online learning sites. (©2010) - Unknown
No abstract available